ChemInform Abstract: KSbI6O18: An Antimony Iodate Semiconductor Material with Cyclic Chiral S6‐Symmetric Hexaiodate. Issue 16 (March 2016) - He, Guo‐Xiang; Chen, Yi‐gang; Yang, Nan; Xing, Mei‐Ling; Zhang, Xian‐Ming
Abstract: The novel title compound is hydrothermally synthesized from a mixture of Sb2 O3, K2 CO3, I2 O5, and H2 O (autoclave, 210 °C, 4 d, 98% yield).